Simulasi Desain Fasad Optimal Terhadap Pencahayaan Alami Pada Gedung Prodi Arsitektur Universitas Malikussaleh - Atthaillah Atthaillah; Suhartina Wijayanti; Soraya Masthura Hassan (EMARA: Indonesian Journal of Architecture, 2018)
The department of architecture’s building of Malikussaleh University was found problematic with its daylighting distribution through out the spaces. Also, earlier research had acknowledged the situation. However, the previous research did not offer an appropriate solution particularly regarding its optimum façade design. This research attempted to optimize the daylight harvest into the spaces by comparing its façade design for daylighting. There were three types of façade designs, perforated, vertical and horizontal screens, examined fot its most optimum daylight harvest. This study utilized digital simulation using Grasshopper and Ladybug Tools to calculate Annual daylight condition within the building. Within the tools this study integrated Climate Based Daylight Modeling (CBDM), which was Useful Daylight Illuminance (UDI) for the condition of Lhokseumawe. Next, it compared and suggested the result for the three types of façade design for optimum daylight distribution. Based on UDI, the targetted optimum daylight was in the range of 100-2000 lux. It was discovered that horizontal screen work best to almost entire building façades which covered 13 out of 15 examined-spaces within the building.